Il libro dei miraggi - Jolanda, 1864-1917 (Salt Lake City, UT : Project Gutenberg, 2022)
"Il libro dei miraggi" by Jolanda is a novel written in the late 19th century. The story primarily focuses on the character Clotilde, a young woman deeply committed to her medical studies and driven by a strong sense of compassion and purpose. Throughout the narrative, themes of gender expectations, societal pressures, and the tension between personal aspirations and familial responsibilities are explored. The opening of the novel introduces Clotilde in her domestic setting, interacting with her brother Roberto and their grandmother. As she navigates the challenges posed by her ambitions in medicine, Clotilde also faces criticism and misunderstanding from those around her. Her internal struggles reflect her desire to balance her pursuit of knowledge and her calling to help others, alongside her emerging feelings for Aroldo, a fellow student. The initial chapters establish the atmosphere of the period and set the stage for her journey through love, loss, and self-discovery amidst the complexities of her life and career in a male-dominated field. (This is an automatically generated summary.)
Release date is 2022-03-04
Barbara Magni and the Online Distributed Proofreading Team at http://www.pgdp.net (This file was produced from images made available by The Internet Archive)
Keywords: Italian fiction -- 19th century